Antibodies directed against bacterial antigens in sera of Polish patients with primary biliary cholangitis - Bauer, Alicja; Habior, Andrzej (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPrimary biliary cholangitis (PBC) is a cholestatic, autoimmune liver disease with the presence of characteristic autoantibodies. The aim of the work was to determine the level of antibodies directed against bacterial antigens: Chlamydia pneumoniae (anti-Cpn), Yersinia enterolitica (anti-Y.e), Helicobacter pylori (anti-Hp), Mycoplasma pneumoniae (anti- Mp.) and Escherichia coli (E.coli) in sera of PBC patients. We also performed in vitro studies on the impact of the bacterial peptides on the specific antigen-antibody binding.MethodWe screened 92 Polish PBC patients and sera samples from healthy donors and pathological controls. Autoantibodies and anti-bacterial antibodies were determined by commercially available ELISA kits. Specific inhibition of antibody binding was also detected by the in house ELISA method.ResultsAnti-Cpn, anti-Y. enterolitica, anti-Hp, anti-M. pneumoniae and anti-E. coli antibodies were significantly more common in the group of PBC patients than in the pathological and healthy control groups: 74%, 40%, 84%, 39% and 69% respectively. The mean level of anti-Cpn, anti- Y.e, anti-Hp and anti- M.p in the PBC group was significantly higher than those in the healthy group (p < 0.001). and in patients with other liver diseases. In sera of patients with the presence of positive anti-mitochondrial antibodies (AMA), specific for PBC, anti-bacterial antibodies have been found in 80% vs. 50% in sera with AMA negative. We observed inhibition of specific antigen-antibody binding by the bacterial peptide: EClpP (E. coli caseinolytic protease) and adenine glycosylase from E. coli caseinolytic protease P, ClpP Y.e from peptide of Y. enterolitica, Mp PDC from M. pneumonia peptide and adenine glycosylase of E. coli. Bacterial factors influence the specific binding of antibodies to pyruvate dehydrogenase (PDC-E2), gp210 and KLHL12 (kelch-like peptide 12) antigens.ConclusionMicrobial mimics may be the major targets of cross-reactivity with human pyruvate dehydrogenase, gp210, and KLHL12 in PBC.